2016
DOI: 10.17557/tjfc.82794
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Nitrogen Doses and Irrigation Levels on Yield, Nutritive Value, Fermentation and Gas Production of Corn Silage

Abstract: The study was conducted to investigate the effects of different irrigation levels and nitrogen doses on yield, yield parameters, silage characteristics, digestibility, gas and methane production of corn silage. Three different irrigation levels (50%, 75% and 100% of depleted water) and 3 different nitrogen doses (100, 200 and 300 kg ha-1 N) were applied to corn silage. Experiments were implemented in split-split plots design with three replications during the growing seasons of 2013-2014. Plants were harvested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 36 publications
(41 reference statements)
5
19
0
1
Order By: Relevance
“…Probably, N fertilization increased the number of lactic acid bacteria, especially those with a high capacity for acid production, in the silage by increasing CP concentration in the forage (McDonald et al, 1991). In agreement with findings in this study, Kaplan et al (2016) reported that, in addition to its positive effects on silage fermentation, N supply slightly increased the lactic acid content but decreased pH levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Probably, N fertilization increased the number of lactic acid bacteria, especially those with a high capacity for acid production, in the silage by increasing CP concentration in the forage (McDonald et al, 1991). In agreement with findings in this study, Kaplan et al (2016) reported that, in addition to its positive effects on silage fermentation, N supply slightly increased the lactic acid content but decreased pH levels.…”
Section: Discussionsupporting
confidence: 93%
“…Silage is highly nutritive and easily digested by livestock due to its good fermentation (Tukel & Hatipoglu, 1997). Additionally, silage can be used in a variety of nutritional programmes, and its protein is cheaper than that supplied by mixed feeds and supplies a high pro‐vitamin A content (Kaplan et al, 2016; Tumer, 2001). Amer and Mustafa (2010) reported that, relative to maize ( Zea mays L.) silage, millet silage contains higher quantities of crude protein (13.0% vs. 9.4%), neutral detergent fibre (66.9% vs. 40.7%) and acid detergent fibre (38.8% vs. 23.9%).…”
Section: Introductionmentioning
confidence: 99%
“…The environments with high silage yields have also the other traits at high rates. Besides silage yields of silage maize genotypes, cob, stem and leaf ratios were indicated as significant factors influencing the quality (Kaplan et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen plays significant roles in chlorophyll, enzymes and thus in plant growth and development. Several previous studies indicated the role of nitrogen in improving crop yields, plant protein contents and nutrient uptake of soybean (Kaplan et al, 2016;Kökten et al, 2014).…”
Section: Introductionmentioning
confidence: 99%